Cognitive and motor performance in Congolese children with konzo during 4 years of follow-up: a longitudinal analysis - Prof Michael J Boivin, PhD; Daniel Okitundu, MD; Bumoko Makila-Mabe, MD; Marie-Therese Sombo, MD; Prof Dieudonne Mumba, PhD; Prof Alla Sikorskii, PhD; Prof Banea Mayambu, PhD; Prof Desire Tshala-Katumbay, PhD (Elsevier, 2017)
Background: Konzo is an irreversible upper-motor neuron disorder affecting children dependent on bitter cassava for food. The neurocognitive ability of children with konzo over time has yet to be fully documented. Methods: We did a longitudinal study in a konzo outbreak zone continuously affected by konzo since 1990, in the district of Kahemba, southern Bandundu Province, Congo. We enrolled children with a record of neurological diagnosis of konzo in Kahemba town. For all study children with konzo enrolled in the final sample for the baseline assessment, a neurological exam was done by neurologists to confirm konzo diagnosis using the 1996 WHO criteria at 2 years and 4 years. In the initial baseline sample for each child with konzo, we attempted to get consent from a comparison child without konzo (1996 WHO criteria) within 2 years of age, from a neighbouring household who met inclusion criteria. The neuropsychological assessments were the Kaufman Assessment Battery for Children, second edition (KABC-II), and the Bruininks-Oseretsky Test of Motor Proficiency, second edition (BOT-2). Findings: Data collection occurred between Oct 12, 2011, and Aug 14, 2015, in the town of Kahemba. 123 children from the Congo with konzo and 87 presumably healthy children without konzo from neighbouring households were enrolled. The planned assessments were completed by 76 children with konzo and 82 children without konzo at 2-year follow-up, and by 55 children with konzo and 33 children without konzo at 4-year follow-up. Boys with konzo did worse than those without konzo on the KABC-II Learning (p=0·0424) and on the Mental Processing Index (MPI; p=0·0111) assessments at 2-year follow-up, but girls did not. These differences observed in boys might have been caused by stunting. At 4-year follow-up, the difference in KABC-II MPI score between boys or girls with or without konzo was not significant. Both boys and girls with konzo had lower scores on BOT-2 than children without konzo at both follow-up times (p<0·0001). These differences were not attenuated when controlling for physical growth. Boys with and without konzo declined on BOT-2 fine motor proficiency at 2-year follow-up (boys with konzo p=0·0076; boys without konzo p=0·0224) and KABC-II MPI performance at 2-year follow-up and 4-year follow-up (2 years: boys with konzo p<0·0001, boys without konzo p=0·0213; 4 years: boys with konzo p=0·0256, boys without konzo p=0·10), but that was not the case for the girls with scores remaining stable regardless of konzo status. For boys, increases in urinary thiocyanate concentration was significantly associated with reductions in BOT-2 motor proficiency (p=0·0321), but was not significantly associated in girls and urinary thiocyanate concentration was not associated with KABC-II MPI score for either boys or girls. Interpretation: Motor and cognitive performance continues to be significantly impaired in boys with konzo at 2-year follow-up compared with boys without konzo. Because these impairments are associated in part with exposure to poorly processed cassava as measured by urinary thiocyanate, interventions are urgently needed to ensure improved processing of cassava to detoxify this food source. Funding: US National Institutes of Health.